OPTIMIZING SOUND DESIGN IN RADIO PROGRAM PRODUCTION TO INCREASE BROADCAST ATTRACTIVENESS - Tuty Mutiah,; Ali Imron Hamid,; Syarif Fitri, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The development of audio technology and the growing competition among digital media platforms have compelled radio stations to continuously innovate in producing engaging and high-quality broadcasts. One key aspect in creating broadcast appeal is the optimal application of sound design. This study aims to analyze the role and strategies of optimizing sound design in the production of non-news radio programs, as well as to explore how sound elements such as jingles, bumpers, sound effects, and background music contribute to enhancing the listening experience. This research employs a qualitative approach using a case study method at a selected radio station in Jakarta. Data were collected through in-depth interviews with producers, audio engineers, and listeners, as well as through direct observation of the production process. The findings reveal that creatively and consistently designed sound elements strengthen program identity, build emotional atmosphere, and increase listener engagement. The optimization of sound design depends not only on technical proficiency but also on the production team’s ability to understand the audience’s characteristics and the program’s context. Therefore, sound design serves as a strategic component in enhancing the aesthetic and emotional value of radio programs in the era of media convergence.